Tissue-Specific Expression Pattern in Ancherythroculter nigrocauda, a Sexually Size Dimorphic Fish - Sun, Yanhong; Wei, Huijie; Chen, Jian; Li, Pei; Yang, Qing; Wang, Guiying; Li, Qing (Frontiers in Genetics, 2021)
Certain members of the Actinopterygii class are known to exhibit sexual dimorphism (SD) that results in major phenotypic differences between male and female fishes of a species. One of the most common differences between the two sexes is in body weight, a factor with a high economic value in aquaculture. In this study, we used RNA sequencing (RNA-seq) to study the liver and brain transcriptomes of Ancherythroculter nigrocauda, a fish exhibiting SD. Females attain about fourfold body weight of males at sexual maturity. Sample clustering showed that both sexes were grouped well with their sex phenotypes. In addition, 2,395 and 457 differentially expressed genes (DEGs) were identified in the liver and brain tissues, respectively. The gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses predicted the association of PPAR signaling, cytochrome P450, and steroid hormone biosynthesis to the differences in sexual size. In addition, weighted gene co-expression network analyses (WGCNA) were conducted, and the green module was identified to be significantly correlated with sexual size dimorphism (SSD). Altogether, these results improve our understanding of the molecular mechanism underlying SSD in A. nigrocauda.